2002
DOI: 10.1159/000064949
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Dysfunction in Multiple Sclerosis: Correlation with Disease-Related Parameters

Abstract: Cardiovascular autonomic functions were investigated in a prospective, controlled study of 22 consecutive relapsing-remitting multiple sclerosis (MS) patients and 22 healthy subjects using 5 simple noninvasive tests and sympathetic skin response testing. Tests included the heart rate response to deep breathing, valsalva maneuver and standing, blood pressure response to standing and sustained hand grip, and were graded according to the Ewing and Clark classification as early, definite or severe impairment. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 14 publications
5
52
0
Order By: Relevance
“…7,14,15 The percentage of patients complaining about gastrointestinal symptoms was the highest of all domains. This finding supported former studies showing that gastrointestinaldysfunction is a common feature in MS patients, who tend to have slowergastric emptying rate16 as well as bowel symptoms 17,18 Previous evidence showed that orthostatic intolerance can be present in up to 50% of MS patients 19 and in our study it affected around 60%.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…7,14,15 The percentage of patients complaining about gastrointestinal symptoms was the highest of all domains. This finding supported former studies showing that gastrointestinaldysfunction is a common feature in MS patients, who tend to have slowergastric emptying rate16 as well as bowel symptoms 17,18 Previous evidence showed that orthostatic intolerance can be present in up to 50% of MS patients 19 and in our study it affected around 60%.…”
Section: Discussionmentioning
confidence: 96%
“…1 The autonomic nervous system dysfunction (ANSD) is commonly seen in patients with MS and is characterized by bladder and gastrointestinal disturbances, sexual dysfunction, abnormalities in cardiovascular function and sudomotor disorders. [1][2][3][4][5][6][7] These symptoms may have a significant impact in patients' quality of life and should be explored as part of the routine evaluation. [1][2][3][4][5]8 Neurological disability assessed by Expanded Disability Status Scale Revista Científica da Ordem dos Médicos www.actamedicaportuguesa.com Vieira B, et al Prevalence of autonomic dysfunction in patients with multiple sclerosis, Acta Med Port 2015 Jan-Feb;28(1): [51][52][53][54][55] (EDSS) focuses mainly on the somatic nervous system and undervalues the role of autonomic failure, only taking into account bladder and bowel dysfunction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the pathophysiology of MS is characterized by dissemination in space, as well as in time, the autonomic nervous system is inevitably damaged in the course of the disease in many patients and the proportion of affected patients increases with disease duration [2].…”
Section: Introductionmentioning
confidence: 99%